Role of Androgen on Physiological Function of Pilosebaceous Unit - Inda Astri Aryani; Cayadi Sidarta Antonius; Suroso Adi Nugroho; Nopriyati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
The pilosebaceous unit is a sebaceous gland with hair follicles. One of the hormones that affects the pilosebaceous unit is androgen, a steroid hormone that plays an important role in the expression of the phenotype of men and women. Androgen consist of testosterone and dihydrotestosterone which are activated by androgen receptors. Androgen in the pilosebaceous unit affect sebum production and hair growth. Androgen receptors in the sebaceous glands are found on sebocytes and in hair follicles in the dermal papillae of hair follicles